MENINGKATKAN KREATIVITAS DAN IMAJINASI ANAK USIA DINI MELALUI MUSIC WALL - Salsabila Rizqi Ramadhanty Alisa; Arvinda Hanugraheningtias; Arnandiza Amirul Khafida; Yuli Kurniawati Sugiyo Pranoto; Deasylina Da Ary (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
This community service aims to improve early childhood creativity and imagination through the implementation of interactive learning media in the form of Music Wall. The background of this activity is based on the limited play media that can stimulate children's creative expression in PAUD institutions, especially those in areas with limited resources. Music Wall is designed using used items such as pots, cans, paralon, and wooden spoons arranged to resemble a musical wall, so that children can play while exploring sounds and rhythms. The service activities were carried out through a participatory approach with the stages of initial observation, interviews, planning, implementation, and evaluation. The results of the activity showed that children were very enthusiastic in exploring the Music Wall and showed improvement in aspects of creativity, fine motor skills, and cooperation skills. Teachers also felt the positive benefits of using this media as it made learning more fun and meaningful. In addition, this media encourages the involvement of teachers and parents in creating a more participatory and contextualized learning environment. Based on these results, Music Wall is recommended as an alternative learning media that is cheap, child-friendly, and easily replicated in various PAUD institutions. This activity is expected to inspire more creative learning transformation in early childhood education.